Age and Growth of the Silver Scabbardfish, Lepidopus caudatus (Euphrasen, 1788), in the Eastern Adriatic - Ines Rebac; Josipa Ferri (Fishes)
The age, growth and otolith morphometry of Lepidopus caudatus were studied by investigating the sagittal otoliths of specimens collected in the eastern Adriatic. A total of 295 specimens, ranging from 20.7 to 123.0 cm in total length (TL), were analysed. Ground otoliths displayed a typical pattern of opaque and translucent alternated zones. The whole population was dominated by 0+-year-old fish, and the maximum observed age was four years. The oldest individuals in the sample were males. The total length-at-age was described by the von Bertalanffy growth model: TL = 134.98[1 − exp (−0.32(t + 1.01))]. Based on the model, we estimated the longevity of the fish, which was 8.35 years. Otolith length, width, thickness and mass were linear with fish TL and age. The most accurate age estimate for the analysed population was derived from the otolith length. Comparisons with available studies from the Mediterranean and other areas are discussed.